Hemoglobin E genotypes and fertility: a study among the Ahom of Upper Assam, India - Das, Bhaskar; Sengupta, Sarthak (International Journal of Research in Medical Sciences, 2017)
Background: Differential fertility is reported in areas where prevalence of hemoglobin E (Hb E) is high. At this backdrop a representative Ahom sample from Upper Assam is studied to examine if differential fertility exist between Hb E and normal Hb A mothers and whether there is significant difference between them with regard to the hemoglobin (Hb) concentration. Methods: Detailed reproductive histories are collected from 119 Ahom couples followed by Hb typing by ‘Cellulose Acetate Gel’ electrophoresis (pH 8.9) and fetal hemoglobin (Hb F) determined by Acid Elution technique. Hb concentration (in g/dl) is measured by Sahley’s method. Results: The calculated Hb E allele frequencies for the Ahom male and the female subjects are 0.424 and 0.403 respectively. β-carrier frequency in the total sample is found to be 0.42%. There is no differential fertility observed between Hb A/Hb A (AA), Hb A/Hb E (AE) and Hb E/Hb E (EE) mothers. Reproductive performance of the couples revealed that the mothers with an Hb E complement either heterozygous or homozygous are more likely to have a spontaneous abortion or an infant mortality. Conclusions: It may be concluded that Hb E induced anemia may increase spontaneous abortion and infant mortality in AE and EE mothers.